The development of teacher creativity in making creative learning materials at experimental state elementary school 2 Sleman - Noer Doddy Irmawati; Rendra Widyatama; Maya Ulyani; Peni Larasati (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
In the era of the Covid-19, distance learning with interesting learning materials is needed to avoid boredom and burnout. Online distance learning requires the use of the internet and the readiness of teachers to process learning materials. In reality, internet use is limited to teachers and students in urban areas that have better information and technology. Therefore, the development of teacher creativity in making creative learning materials, especially in making creative media, needs to be used as a follow-up to overcome Online learning problems. Internet information technology, which was previously used as a source of information, must now be used as a media aid in Online learning, especially at the level of basic education. After a 42-hour workshop with discussions; (1) Creative and interesting learning with a literary approach; (2) Making interesting and creative learning media, and; (3) Learning technology and its handling. The teachers of Experimental State Elementary School 2 have obtained recipes for making creative learning media that are able to attract stronger attention to children when participating in online learning.  Teachers have also been able to prepare PowerPoint for interesting and not boring subjects